2022
DOI: 10.1186/s12951-022-01521-7
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency vibrating magnetic field-triggered magnetic microspheres with a nanoflagellum-like surface for cancer therapy

Abstract: Background The magneto-mechanical force killing cancer cells is an interesting and important strategy for cancer therapy. Results Novel magnetic microspheres composed of a Fe3O4 nanocore, a bovine serum albumin (BSA) matrix, and a rod-like SiO2 nanoshell, which had flagellum-like surface for force-mediated cancer therapy were developed. One such magnetic microsphere (Fe3O4/BSA/rSiO2) at a cancer cell (not leave the cell surface) under a low frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The magneto-mechanical effect provided by MNPs under low-frequency magnetic field exposure is a growing field of research in biomedicine. It can be used in regenerative medicine and tissue engineering [34], in biomedicine for enzyme activity and cell receptor control, as well as for mechanically activated drug release [9,35], and in cancer therapy [21,36,37]. Different types of MNPs have been designed for specified purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The magneto-mechanical effect provided by MNPs under low-frequency magnetic field exposure is a growing field of research in biomedicine. It can be used in regenerative medicine and tissue engineering [34], in biomedicine for enzyme activity and cell receptor control, as well as for mechanically activated drug release [9,35], and in cancer therapy [21,36,37]. Different types of MNPs have been designed for specified purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they found a synergistic cytotoxic effect arising from the combination of a chemotoxic and magneto–mechanical treatment (1 mT, 10 Hz). Guo found magnetic hybridized microparticles (i.e., Fe 3 O 4 /BSA/rSiO 2 ; Figure 6 ) with a flagellum-like surface as force-mediated cancer treatment [ 104 ]. The cell killing efficiency increased with increasing magnetic field frequency (≤3 Hz), vibrating magnetic field (VMF) exposure time (≤1.5 h), and microsphere concentration.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Fe 3 O 4 /BSA, Fe 3 O 4 /BSA/SrSiO 2 , Fe 3 O 4 /BSA/MrSiO 2 , Fe 3 O 4 /BSA/LrSiO 2 , and Fe 3 O 4 /BSA/CrSiO 2 are numbered ➀, ➁, ➂, ➃, and ➄, respectively. Reprinted from [ 104 ].…”
Section: Cancer Therapymentioning
confidence: 99%
“…Найнижче значення модуля Юнга в пухлині обумовлено застосуванням аплікатора з постійним магнітом, яке сприяло розподілу МНЧ в опроміненій ділянці за градієнтом ПМП [23] та подальшому захопленню МНЧ фагоцитами [24], їх евакуації разом з клітинним детритом [25]. По-друге, під впливом магнітної сили виникають локальні механічні зміни і підвищення концентрації активних форм кисню та азоту, що, у свою чергу, викликає порушення білкових і ліпідних клітинних структур, апоптоз та некроз у клітинах пухлини з МНЧ [26]. У раніше опублікованих роботах показано, що параметр жорсткості пухлин HBCx-3 моделі раку молочної залози людини у безтимусних мишей nude зменшувався зі збільшенням вираженості некрозу та, навпаки, зростав у разі переважання фіброзного заміщення тканин пухлини [27].…”
Section: результати та обговоренняunclassified